Do terrestrial hermit crabs sniff? Air flow and odorant capture by flicking antennules - Waldrop, Lindsay D. (J R Soc Interface, 2016)
Capture of odorant molecules by olfactory organs from the surrounding fluid is the first step of smelling. Sniffing intermittently moves fluid across sensory surfaces, increasing delivery rates of molecules to chemosensory receptors and providing discrete odour samples. Aquatic malacostracan crustaceans sniff by flicking olfactory antennules bearing arrays of chemosensory hairs (aesthetascs), capturing water in the arrays during downstroke and holding the sample during return stroke. Terrestrial malacostracans also flick antennules, but how their flicking affects odour capture from air is not understood. The terrestrial hermit crab, Coenobita rugosus, uses antennules bearing shingle-shaped aesthetascs to capture odours. We used particle image velocimetry to measure fine-scale fluid flow relative to a dynamically scaled physical model of a flicking antennule, and computational simulations to calculate diffusion to aesthetascs by odorant molecules carried in that flow. Air does not flow into the aesthetasc array during flick downstrokes or recovery strokes. Odorants are captured from air flowing around the outside of the array during flick downstrokes, when aesthetascs face upstream and molecule capture rates are 21% higher than for stationary antennules. Bursts of flicking followed by pauses deliver discrete odour samples to olfactory sensors, causing intermittency in odour capture by a different mechanism than aquatic crustaceans use.